The Influence of Transformational Leadership Style, Work Motivation, Employee Performance, and Perceived Meaningfulness of Work - Ginka Febriyanti Br Ginting; Dian Alfia Purwandari; Rina Anindita (Eduvest - Journal of Universal Studies, 2026)
This research was conducted to explore the effects of Transformational Leadership Style on employee performance, Transformational Leadership Style on work motivation, work motivation on employee performance, Transformational Leadership Style on employee performance with motivation as a mediating variable, Transformational Leadership Style on perceived meaningfulness of work, and perceived meaningfulness of work on work motivation. This study uses a quantitative approach with a survey method, distributing online questionnaires to 325 employees working in the administrative staff section of manufacturing industry head offices in the DKI Jakarta area. Respondents for this study were selected using a purposive sampling method. The data were analyzed using the Structural Equation Model (SEM) technique. The results of this study indicate that Transformational Leadership Style has no direct effect on employee performance; however, it has a significant effect on work motivation. Work motivation, in turn, influences employee performance and mediates the relationship between Transformational Leadership Style and employee performance. Furthermore, Transformational Leadership Style affects the perceived meaningfulness of work, while the perception of meaningfulness of work significantly affects work motivation. The managerial implications of this research suggest that company management should strengthen employees’ work motivation to encourage greater creativity and improve overall performance.